Optimized Design of an ECAP Die Using the Finite Element Method for Obtaining Nanostructured Materials - Patricia Ponce-Peña; Edgar López-Chipres; Edgar García-Sánchez; Miguel Angel Escobedo-Bretado; Brenda Xiomara Ochoa-Salazar; María Azucena González-Lozano (Advances in Materials Science and Engineering)
An alloy type A16060 was exposed to severe plastic deformation to study its reaction using the finite element method (FEM). To perform this, six different configurations were used in the design of the die’s channel for ECAP (equal channel angular pressing) to obtain nanostructure materials and to optimize the process. Thanks to simulation performed with FEM, it is possible to study the homogeneity in the deformation due to the variation of conditions affecting directly the material being processed using the ECAP technique, such as the friction coefficient, extrusion speed, and mainly the die’s channel geometry being utilized in the ECAP process. Due to the tensile strain area being located mainly in the upper part of the deformed test cylinder (plastic deformation area) which increases the fracture and cracking tendency preventing the processing through ECAP the die being utilized was modified to eliminate the tensile strain area favoring the appearance of compressive stress which reduces the cracking tendency and the fracture of the sample being processed. The FEM analysis demonstrated that the strain state changed significantly from tension to compression when the modified die was used, facilitating the processing of the piece by ECAP.